Religiusity the Community of Kampung Adat Cireundeu, Cimahi, Jawa Barat - Siti Nurhasanah (International Journal of Nusantara Islam, 2019)
The life of Indigenous people has an interesting social situation and religiosity to study. This paper aims to examine: (1) Religiosity (2) Religious patterns, (2) Conservation of religious values of Cireundu traditional village communities. This study uses a qualitative approach with descriptive analytical methods about local religious struggles, namely Sunda Wiwitan with the influence of the surrounding environment, in the perspective of sociology it focuses more on religious phenomena that occur between modernization and adherents of local religions. Data collection is done through: (a) Participatory observation (participant observation), (b) In-depth interviews. (c) Documentation. Religion as "mode is for reality" provides a "framework" for seeing reality, religion provides "system of meaning" for its socially produced followers. The Cireundeu indigenous people tend to make "religion" as "the ultimate concern". They make religion a fundamental philosophy in their lives. Almost all activities in their lives are based on religious values.